3D-printed monolithic catalyst of Mn-Ce-Fe/attapulgite for selective catalytic reduction of nitric oxide with ammonia at low temperature. Issue 4 (August 2021) - Li, Yanqin; Jiang, Pan; Tian, Junqi; Liu, Ying; Wan, Yinji; Zhang, Ke; Wang, Denghao; Dan, Jianming; Dai, Bin; Wang, Xiaolong; Yu, Feng
Abstract: An alternative method was taken to fabricate Mn-Ce-Fe/attapulgite (ATP) monolithic catalysts employing a direct ink writing (DIW) 3D printing technique for selective catalytic reduction reactions with ammonia (NH3 -selective catalytic reduction (SCR)) at low-temperature. In this paper, the effects of different active components on powder catalysts were investigated. The results showed that Mn-Ce-Fe/ATP powder catalyst contained higher Mn 4+ and Oads, and the catalyst included more reducible substances at low temperatures. The Mn-Ce-Fe/ATP powder catalyst exhibited excellent catalytic activity (NO conversion 90%, N2 selectivity 70%) over a wide temperature window range of 100–400 °C. Therefore, a series of Mn-Ce-Fe/ATP monolithic catalysts were prepared by 3D printing. The effects of porosity and space velocity on the performance of the catalysts were investigated. The result showed that the NO removal rates of Mn-Ce-Fe/ATP monolithic catalysts were 50% at 100 °C and 70% at 400 °C when the porosity was 42.82% and the gas hourly space velocity was 2000 h −1 . Graphical Abstract: ga1 Highlights: Mn-Ce-Fe/ATP powder catalyst exhibited excellent catalytic performance in a wide temperature range (100–400 °C). Three-dimensional (3D) printing was employed to prepare Mn-Ce-Fe/ATP monolithic catalyst. The Mn-Ce-Fe/ATP monolithic catalyst performed great NOx removal of 50% even at 100 °C.